Analysis of Significant Type of Compensation Towards Employee Preference in Startup Companies Within Bandung (Journal of Innovation, Business and Entrepreneurship, 2020)
Startup companies are newly born businesses that compete for life. Steve Blank (2010, p. xvii) also mentioned that, “A startup is a temporary organization in search of a scalable, repeatable, profitable business model”. Compensation is arguably one of the most influencing factors on the efficiency and productivity of human capital. The Compensation procedure that mostly used comprise base pay, merit pay, profit sharing, stock option until employee benefit. But the reality in a startup company is also facing a difficulty. One explanation for this difficulty is the minimal resources available to new companies (Bruton & Rubanik, 2002). Consequently, the importance of compensation and deficient situations of a startup, a startup needs to find an efficient way to allocate its limited budget to gain maximum level of employee satisfaction. The researcher thus intended to do study based on two foundations; the difference of employee compensation preference and the significance of each compensations means between each employee level. The researcher conducts quantitative approach by using questionnaire methods. The data gathered then analyzed using One-Way ANOVA. This study could lay the foundations of the understanding of Bandung startup's employee preference towards types of compensation.Keywords: Startups in Bandung, Employee Compensations, Employee Preference